Metal bioleaching from sludge : current status and potential - Anayiotou, Elena (Department of Environmental Science and Technology, Faculty of Geotechnical Sciences and Environmental Management, Cyprus University of Technology, 2015)
The treatment of municipal wastewater results in large amounts of residual sludge and has to be disposed of in a safe and economic way. The most common way of sludge disposal, is land application. However, the downside of these pollutants such as heavy metals, toxic organic compounds and pathogens might be accumulated during conventional sewage treatment process and limits their use for land application. Bioleaching via the solubilisation of metals from solid substrates either directly by the metabolism of leaching bacteria or indirectly by the products of metabolism which has been developed and demonstrated to be an efficient and cost-effective means of removing heavy metals from sewage sludge without seriously affecting its soil conditioning and fertilizing properties. In this review, a study has been conducted on the effects of bioleaching and concentrates on the three different types of sludge that of anaerobically digested sewage sludge, tannery sludge and pig slurry. In addition, the parameters that influence the result of these methods are also looked at. Furthermore, a case study was carried out via the use of an equation that calculates the profit following the sale of heavy metals after bioleaching and their recovery as commodities.
Keywords: Municipal wastewater; Heavy metals; Toxic organic compounds; Pathogens